Research and engineering at the Polski Koncert Naftowy S.A. polypropulene plant at Płock - Kudła, S.; Maciejewska, H.; Uhniat, M.; Majchrzak, Z.; Kurkowska, M.; Wiśniewski, A.; Bańkowski, A. (Polimery, 2022)
The propylene polymerization (30000 ton ton PP/year) installations run on Zielgler-Natta generaton I and II catalysts were modernized by using generation III and IV catalysts, which are highly active and stereoregular. The installations were modernized by eliminating the methanol-water wash step and the methanol recovery step.